Mechanisms influencing the evolution of resistance to Qo inhibitor fungicides - Gisi, U.; Sierotzki, H.; Cook, A.; McCaffery, A.
Fungicides inhibiting the mitochondrial respiration of plant pathogens by binding to the cytochrome bc1 enzyme complex (complex III)at the Qo site (Qo inhibitors, QoIs)were first introduced to the market in 1996. After a short time period, isolates resistant to QoIs were detected in field populations of a range of important plant pathogens including Blumeria graminis Speer f sp tritici, Sphaerotheca fuliginea (Schlecht ex Fr)Poll, Plasmopara viticola (Berk & MA Curtis ex de Bary)Berl & de Toni, Pseudoperonospora cubensis (Berk & MA Curtis)Rost, Mycosphaerella fijiensis Morelet and Venturia inaequalis (Cooke)Wint. In most cases, resistance was conferred by a point mutation in the mitochondrial cytochrome b (cyt b)gene leading to an amino-acid change from glycine to alanine at position 143 (G143A), although additional mutations and mechanisms have been claimed in a number of organisms. Transformation of sensitive protoplasts of M fijiensis with a DNA fragment of a resistant M fijiensis isolate containing the mutation yielded fully resistant transformants, demonstrating that the G143A substitution may be the most powerful transversion in the cyt b gene conferring resistance. The G143A substitution is claimed not to affect the activity of the enzyme, suggesting that resistant individuals may not suffer from a significant fitness penalty, as was demonstrated in B graminis f sp tritici. It is not known whether this observation applies also for other pathogen species expressing the G143A substitution. Since fungal cells contain a large number of mitochondria, early mitotic events in the evolution of resistance to QoIs have to be considered, such as mutation frequency (claimed to be higher in mitochondrial than nuclear DNA), intracellular proliferation of mitochondria in the heteroplasmatic cell stage, and cell to cell donation of mutated mitochondria. Since the cyt b gene is located in the mitochondrial genome, inheritance of resistance in filamentous fungi is expected to be non-Mendelian and, therefore, in most species uniparental. In the isogamous fungus B graminis f sp tritici, crosses of sensitive and resistant parents yielded cleistothecia containing either sensitive or resistant ascospores and the segregation pattern for resistance in the F1 progeny population was 1:1. In the anisogamous fungus V inaequalis, donation of resistance was maternal and the segregation ratio 1:0. In random mating populations, the sex ratio (mating type distribution)is generally assumed to be 1:1. Therefore, the overall proportion of sensitive and resistant individuals in unselected populations is expected to be 1:1. Evolution of resistance to QoIs will depend mainly on early mitotic events; the selection process for resistant mutants in populations exposed to QoI treatments may follow mechanisms similar to those described for resistance controlled by single nuclear genes in other fungicide classes. It will remain important to understand how the mitochondrial nature of QoI resistance and factors such as mutation, recombination, selection and migration might influence the evolution of QoI resistance in different plant pathogens.
Keywords: STROBILURIN FUNGICIDES; FUNGICIDE RESISTANCE; QO INHIBITORS; CYTOCHROME B; MITOCHONDRIAL INHERITANCE; UNIPARENTAL INHERITANCE